THE INFLUENCE OF HERRINGBONE TECHNIQUE TOWARDS THE READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMPN 4 SIAK HULU - Yuzulia, Irza; ', Mahdum Ph. D; ', Eliwarti, M. App.ling (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental research aimed to find out whether there is significant influence of students? reading comprehension after using Herringbone Technique in teaching reading at the second year of SMPN 4 Siak Hulu. Thus, the problem to be discussed is whether or not there is any significant influence of the students? reading comprehension after using Herringbone Technique in teaching reading at the second year of SMPN 4 Siak Hulu. The design of the research was one group pretest-posttest design. Cluster random sampling method was used to select one class to be the sample. As a result, 36 students of class VIII A at the second semester of academic year 2015/2016 were chosen as the sample. The steps applied in using herringbone technique are: (1) The teacher gives a brainstorming for the students by showing them a picture of animal related to the text (2) The teacher asks students? opinion about the picture (3) The teacher asks students to make groups (4) The students read the text to find the answers and record the answers on the diagram (5) The students write the main idea (6) The teacher guides class discussion. The instrument used was a reading test that consists of 38 questions and the obtained data were analyzed by using SPSS version 16.0 for Windows. The results of data analysis are t-test (13.58) was greater than t-table (2.042). This illustrates that there is significant influence of students? reading comprehension after being taught using Herringbone Technique in teaching reading.Keywords: reading comprehension, herringbone technique